2022
DOI: 10.3390/ijms23031903
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis and Transport of Ophiobolins in Aspergillus ustus 094102

Abstract: Ophiobolins are a group of sesterterpenoids with a 5-8-5 tricyclic skeleton. They exhibit a significant cytotoxicity and present potential medicinal prospects. However, the biosynthesis and transport mechanisms of these valuable compounds have not been fully resolved. Herein, based on a transcriptome analysis, gene inactivation, heterologous expression and feeding experiments, we fully explain the biosynthesis pathway of ophiobolin K in Aspergillus ustus 094102, especially proved to be an unclustered oxidase O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…This study completely clarified the biosynthesis mechanism of ophiobolins in the strain of A. ustus and showed that the burden of strain growth caused by the excessive accumulation and toxicity of secondary metabolites is close to compartmentalized biosynthesis. 27…”
Section: Ophiobolin Amentioning
confidence: 99%
“…This study completely clarified the biosynthesis mechanism of ophiobolins in the strain of A. ustus and showed that the burden of strain growth caused by the excessive accumulation and toxicity of secondary metabolites is close to compartmentalized biosynthesis. 27…”
Section: Ophiobolin Amentioning
confidence: 99%
“…Zhang and co‐workers also proposed a biosynthetic pathway in which 1 and 2 can be derived from ophiobolin F ( 7 ) (Scheme 1A) [2,11–13] . Ophiobolin F ( 7 ) undergoes a series of selective enzymatic oxidations to afford intermediate A , in which the A‐ring is flipped to the bottom of the B‐ring and undergoes a key Prins reaction to generate intermediate B bearing a 5/6/6/5 caged carbon skeleton.…”
Section: Figurementioning
confidence: 99%
“…Since ophiobolin A (also called cochliobolin) was firstly discovered in 1957, more than 100 ophiobolins have been isolated and identified from pathogenic fungi of the Bipolaris and Aspergillus genus [1] . Notably, 6‐ epi ‐ophiobolins (C6 α‐H) were biosynthetically produced by the non‐enzymatic transformation of the corresponding natural ophiobolins (C6 β‐H) [2] . It is most likely that the cis ‐5/8 cyclic system possesses higher ring strain and the C6 configuration is readily epimerized to produce the more stable trans ‐5/8 cyclic system.…”
Section: Figurementioning
confidence: 99%
“…[1] Notably, 6-epi-ophiobolins (C6 α-H) were biosynthetically produced by the non-enzymatic transformation of the corresponding natural ophiobolins (C6 β-H). [2] It is most likely that the cis-5/8 cyclic system possesses higher ring strain and the C6 configuration is readily epimerized to produce the more stable trans-5/8 cyclic system. The ophiobolins display a broad spectrum of biological and pharmacological characteristics such as phytotoxic, cytotoxic, antimicrobial, anti-influenza and inflammation-promoting activities.…”
mentioning
confidence: 99%
“…Zhang and co-workers also proposed a biosynthetic pathway in which 1 and 2 can be derived from ophiobolin F (7) (Scheme 1A). [2,[11][12][13] Ophiobolin F (7) In connection with our ongoing studies towards biomimetic synthesis of complex natural products, [14] inspired by Zhang's biogenetic hypothesis, we envisioned that Prins reaction/ether formation cascade cyclization could be applied to construct 5/6/6/5 caged carbon skeleton and C3À C12 oxygen bridge in one step, thus streamline the total synthesis of bipolarolides A (1) and B (2) (Scheme 1 B, 9 to 8). [15] Moreover, cis-A, B ring system is of vital importance for this cascade cyclization, which can bring the ketone and tertiary alcohol closer to cyclopentadiene.…”
mentioning
confidence: 99%